Assessment of Effects of Economic Empowerment Programmes On Rural Women in Kachia Local Government Area in Kaduna State, Nigeria (The NOUN Journal of Agricultural Research and Development (NJARD), 2025)
This study examined the assessment of the effects of economic empowerment programme on rural women in Kachia Local Government Area of Kaduna State. Multi-stage sampling procedure was used to select 408 farmers for this study. Data were collected through interview schedule using structured questionnaire and Focus Group Discussion (FGD).  Both descriptive and inferential statistics was used to analyze the data. Result of the findings reveals that, late loan disbursement, poor extension services and inadequate storage facilities; while inadequate fertilizer supply, poor marketing and inadequate storage facilities were found to be the key impediments to full actualization of Fadama III Development Project in Kachia LGA. The study concludes that the Women Helping Women intervention projects in the study area had more effect on the beneficiaries than Fadama III Development Project being carried out. The study recommends that, Women Helping Women intervention projects should help farmers’ established cooperative association, provision of loans and farm inputs (fertilizers, seeds) and disbursed on time at the onset of farming season to farmers and farmers should form smaller production cluster to improve their market intelligence.